Annotated record and chemical composition of manganese crusts and nodules obtained during Valdivia cruise VA-16/1A-B in early 1977 - Karl Hinz; Helmut Beiersdorf; Neville F Exon; Hans-Albert Roeser; Howard M J Stagg; Ulrich von Stackelberg (PANGAEA, 1978)
The plateau is a foundered continental block, and lies at an average depth of 2000-3000 m. On the plateau the dominant fault direction is NW to WNW, an ancient strike direction on the Australian continent. The western margin probably formed as a series of NE-trending rifts and NW-trending transforms during Late Jurassic breakup. Canyons cut the western margin, and some of these appear to be fault-bounded. One such fault forms the northern margin of a major NW-trending feature, the Wilson Spur. This appears to be a transform fault and perhaps extends across the abyssal plain as far as the eastern end of the Java Trench. Seismic profiles suggest that, at the trench, it separates thrust-faulted continental crust to the east from oceanic crust to the west. This could explain the eastern termintion of the deep part of the trench. The bathymetric depression of the Roti Basin, which lies southeast of the Java Trench, links the trench to the Timor Trough. The Argo Abyssal Plain slopes gently southward, with water depths ranging from 5000 m near the Java Trench to 5730 m in the south. Oceanic basement varies from smooth to hummocky and irregular, and is overlain by about 4000 m of acoustically semi-transparent Late Jurassic and Cretaceous sediments, that is in turn unconformably overlain by 200 m of layered Tertiary sediment. Bottom samples from the outer Scott Plateau show that Callovian breakup was preceded by a period of basic volcanism and shallow marine sedimentation, that restricted shallow marine conditions followed in the Late Jurassic, and that bathyal carbonate sedimenation prevailed by the Late Cretaceous (Campanian). Quaternary marls cored on the northern Scott Plateau straddled the Pleistocene-Holocene boundary, and siliceous oozes cored on the southern slope of the Java Trench contain nannofossils which, below a few decimetres, are older than late Pleistocene. The Java Trench cores indicate that the calcite compensation depth was apparently between 5420 and 5700 m in the early or midel Pleistocene, and is above 4950 m now. The Scott Plateau cores indicate that the present calcite compensation depth in the region lies below 3290 m. On the Scott Plateau Holocene sedimentation rates are about 5 cm/1000 years, but in the Java Trench they are much lower. Manganese oxide crusts and nodules were recovered from the Scott Plateau, but their content of valuable metals was low.
Supplement to: Hinz, K et al. (1978): Geoscientific investigations from the Scott Plateau off northwest Australia to the Java Trench. BMR Journal of Australian Geology and Geophysics, 3(4), 319-340, https://pid.geoscience.gov.au/dataset/ga/80974